Pengaruh Strategi Pengembangan SDM terhadap Daya Saing Organisasi Perguruan Tinggi di Era Transformasi Digital - Feliks Setia Wau; Selvia De Wana (Publikasi Indonesia, 2026)
This study aims to analyze the effect of human resource (HR) development strategies on the competitiveness of higher education institutions in the era of digital transformation. The increasingly dynamic educational environment, characterized by the integration of digital technologies, requires universities to have adaptive, innovative, and competent human resources. This research employs a quantitative approach with an ex post facto design, involving lecturers and educational staff as respondents. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using linear regression to determine the relationship and influence between variables. The results indicate that HR development strategies, including digital-based training, enhancement of technological competencies, and strengthening of organizational culture, have a positive and significant effect on the competitiveness of higher education institutions. Universities that systematically and sustainably develop their human resources tend to be more competitive in facing global challenges, improving the quality of educational services, and strengthening institutional reputation. In addition, digital transformation acts as a supporting variable that strengthens the relationship between HR development and organizational competitiveness. The findings highlight the importance of formulating integrated HR development strategies aligned with institutional digitalization policies to achieve sustainable competitive advantage.